2021
DOI: 10.1108/srj-10-2020-0416
|View full text |Cite
|
Sign up to set email alerts
|

Scale development and validation of total quality and socially responsible management (TQSR-M) framework: dual competitive strategy for management

Abstract: Purpose This study aims to develop a valid and reliable scale for measuring an integrated total quality and socially responsible management (TQSR-M) model, which affects business excellence. Design/methodology/approach Data were collected through a questionnaire in two phases (first for scale development and second for scale validation purpose) from managers employed in Pakistan Stock Exchange (PSX) listed companies. The structural equation modeling technique (SEM) was used to develop and validate the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 123 publications
(176 reference statements)
0
13
0
Order By: Relevance
“…Taking a closer look at TQM and CSR, Benavides-Velasco et al (2014) concluded that both factors positively influence the performance of employees and firms. Among the critical components of TQM, HRM contributes to CSR (Khurshid et al, 2021). However, the relationship between the two variables was insignificant (Nogueiro et al, 2022).…”
Section: Tqm Csr and Green Innovationmentioning
confidence: 97%
“…Taking a closer look at TQM and CSR, Benavides-Velasco et al (2014) concluded that both factors positively influence the performance of employees and firms. Among the critical components of TQM, HRM contributes to CSR (Khurshid et al, 2021). However, the relationship between the two variables was insignificant (Nogueiro et al, 2022).…”
Section: Tqm Csr and Green Innovationmentioning
confidence: 97%
“…The data is collected through a questionnaire survey of managers of listed companies in the Pakistan Stock Exchange (PSX), which is divided into two stages (the first stage is for scale development, and the second stage is for scale verification). Use structural equation modeling (SEM) to define and validate measurement and structural models [8] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Awards and support are given as an appreciation and a constructive motivation for the existence of human resources. Preparing a good workforce is one of the responsibilities that must be fulfilled by organizations for future sustainability processes (Khurshid et al, 2022). Various processes faced by organizations are improved from time to time.…”
Section: Literature Reviewmentioning
confidence: 99%